A Glass Fiber-Reinforced Resin Composite Splint to Stabilize and Replace Teeth in a Periodontally Compromised Patient - Angelika Rauch; Sebastian Mehlhorn; Manja Mühle; Dirk Ziebolz (Hindawi Limited, 2020)
Combined periodontal and prosthodontic treatment demands of patients require a structured coordination of pretreatments and an adequate choice of restorations. This is especially true if multiple teeth are missing and insufficient crown-root ratios are obvious. A 40-year-old patient with a severe periodontitis (Stage IV, Grade C) was treated with active, nonsurgical periodontal therapy. Afterwards, a supportive periodontal therapy was provided with a recall interval of three to four months. Due to a high tooth mobility of the anterior teeth in the upper jaw and a missing left canine, a combination of a resin composite (Signum composite, Kulzer, Hanau, Germany) and a unidirectional glass prepreg fiber (Tender Fiber Quattro, MICERIUM, Avegno, Italy) was utilized to fabricate a splint in a labside approach to stabilize the remaining teeth. Moreover, an artificial denture tooth was adhesively luted to the splint. A temporary polymer-based material (Vita CAD-Temp, VITA Zahnfabrik, Bad Säckingen, Germany) was selected to supply the posterior teeth of the patient with a 3-unit fixed dental prosthesis (FDP), and both restorations were adhesively cemented. 19 months after insertion, a fracture of the fiber-reinforced resin composite splint occurred that was intraorally repaired. In spite of the fracture of the splint, all materials were functionally and esthetically stable over the follow-up period of 22 months.